Interpretacja wyników klasyfikacji obiektów symbolicznych - Wilk, Justyna (Interpretation of Clusters of Symbolic Objects, 2007)
The article characterizes types of symbolic data and a way of interpreting the clusters of symbolic objects. The author also presents how to evaluate the contribution of a cluster to the total variability of the sample, the importance of each variable for each cluster and the contribution of a cluster to the variability of a variable. Moreover the article illustrates the application of "Clint" module of Sodas v. 2.0.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 27-37